The Portrait of Students’ Work in Analysing English Noun Phrase within the Text at English Department FBS Universitas Negeri Padang - Ai Monica; Hermawati Syarif; Fitrawati Fitrawati (English Language Teaching and Research, 2018)
Grouping words into phrases is one of the problems faced by English students in using the language. Noun phrase is a basic constituent of a sentence is seen very problematic. The paper tries to explore how well second year students of English Department analyse noun phrases and their problems in doing it. There were 30 students chosen through proportionate stratified sampling as the sample. The text designed consisting of 20 noun phrases were distributed to the sample to be analysed. Each noun phrase was generally analysed into three aspects, namely, identifying type/component, its function within a sentence, and role of each element. The analysis was by scoring and putting them into percentage. Then, they were categorized into excellent, good, average, poor, and very poor. The result shows that about 60% of sample failed to analyse noun phrase correctly. Their way of analysing noun phrase was in poor level on identifying type/component (45%), its function within a sentence (40.16%), and the role of each element of noun phrase (43%). The problem was mainly students’ lack competence in identifying the part of speech and its function for each point.Key Words: students’ ability, analysis, noun phrase, text